2019
DOI: 10.18203/2394-6040.ijcmph20193977
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index profile among school children: an anthropometric study

Abstract: Background: The study aimed to analyse the trends in the growth pattern of the children in the age group of 3-21 years of both boys and girls using body mass index (BMI). The study also compared the BMI of the sample with the WHO norms and the group average.Methods: A study was conducted in India covering 1728 children 849 boys and 879 girls from LKG grade to +2 grades in the age group of 3-21 years. BMI grades were computed as per WHO 2006 standards (underweight- <18.50, normal- 18.50-24.99, overweight- &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…height and weight are considered vital signs that must be recorded during dental patient examination before surgical procedures or any restorative technique, local anaesthetic injection,or determination of drug doses , height and weight are correlated by certain equation to obtain body mass index that is considered as fat assessment meter while both sever underweight or overweight associated with medical problems [5] throughout this study it is noted that underweight represents the 45% of children in age group more than 10 years while the normal weight children represents 43,5% and this corresponds to the study of et all [6] where this study was carried in assuit governorate that is near to Qena on, tt was on 1000 children and this sudy represents underweight percentage that reaches 67% in some region , also through out our study the two groups below 10 years the underweight percentages reach 85% in (group2 ) and 75%(group2) and also this is in accordance to the study of Mahalakshmi [4] throught this study it is to be noted that the underweight category is less in group1 than in group 2 and this may be due to younger children of group1 stay in home long time and receive more mother care than group2 that begin to stay in schools more hours than group1 through out this study the body mass index, and overweight prevalence increased with age, while underweight prevalence decreased with age and this matches the study of Abd alkarim et al [7] in other studies there is controversy about relation between body mass index and sex studies of both bader et al [8] and Aounallah et al [9] showed that the percentage of overweight was higher among girls compared to boys while the study of Siba et al [10] showed that percentage of overweight was higher among boys compared to girls and these diversity between studies can be explained due to different geoigraphic positios of the studies , different life style genetics and environmental conditions also it is to be noted that overweight and obesity increased from group 2 too group3 with increasing age and this is in accordance to the study of Saleh et al [6] in this study the girls in group3 showed overweight more than boys and this is may be due to decreased girls activity through this study it was noted that the problem of underweight is still young age prevalent problem in in Upper Egypt as stated by the NationalNutrition Institute, 2003, [11] also. These results go in consistence with Osman [12] .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…height and weight are considered vital signs that must be recorded during dental patient examination before surgical procedures or any restorative technique, local anaesthetic injection,or determination of drug doses , height and weight are correlated by certain equation to obtain body mass index that is considered as fat assessment meter while both sever underweight or overweight associated with medical problems [5] throughout this study it is noted that underweight represents the 45% of children in age group more than 10 years while the normal weight children represents 43,5% and this corresponds to the study of et all [6] where this study was carried in assuit governorate that is near to Qena on, tt was on 1000 children and this sudy represents underweight percentage that reaches 67% in some region , also through out our study the two groups below 10 years the underweight percentages reach 85% in (group2 ) and 75%(group2) and also this is in accordance to the study of Mahalakshmi [4] throught this study it is to be noted that the underweight category is less in group1 than in group 2 and this may be due to younger children of group1 stay in home long time and receive more mother care than group2 that begin to stay in schools more hours than group1 through out this study the body mass index, and overweight prevalence increased with age, while underweight prevalence decreased with age and this matches the study of Abd alkarim et al [7] in other studies there is controversy about relation between body mass index and sex studies of both bader et al [8] and Aounallah et al [9] showed that the percentage of overweight was higher among girls compared to boys while the study of Siba et al [10] showed that percentage of overweight was higher among boys compared to girls and these diversity between studies can be explained due to different geoigraphic positios of the studies , different life style genetics and environmental conditions also it is to be noted that overweight and obesity increased from group 2 too group3 with increasing age and this is in accordance to the study of Saleh et al [6] in this study the girls in group3 showed overweight more than boys and this is may be due to decreased girls activity through this study it was noted that the problem of underweight is still young age prevalent problem in in Upper Egypt as stated by the NationalNutrition Institute, 2003, [11] also. These results go in consistence with Osman [12] .…”
Section: Discussionsupporting
confidence: 91%
“…The body mass index is obtained and classified according to the who classes [4] as following And the all the collected information were analyzed using ORIGIN LAP SOFT WARE . 10.6%of group2 was of normal weight followed by 13%of group2 while the group3has the greatest percentage of normal weight which is 43.5% overweight group2 has 2.5% overweight children followed by group 3 (7%) finally group1 has the greatest overweight percentage7% obesity group2 has the least percentage of obesity, followed by 3% in group1 then 5.3% in group3 it is to be noted that overall percentages of different weight was as following 70.7% Underweight, 21.7%normal, 4.3%overweight, 2.9% obesity Table 5 shows that there is a significant relationship between age and BMI between the groups as regard sex distribution boys represented 49% and girls 51% the underweight and normal weight are 72%and 21%respectivey and similar between boys and girls and heavy weight3 is 5% in girls and 4%in boys while obesity is 3% in boys and2%in girls…”
Section: Methodsmentioning
confidence: 99%
“…However, according to a study, age and gender have a significant impact on BMI, so dietary practices should be adapted accordingly. Malnutrition is therefore discovered to be a significant impact in a child's development (Mahalakshmi et al, 2019). Childhood obesity is on the rise, and it's been linked to a variety of disorders and death in adults, thus the body mass index (BMI) has become a popular screening tool for kids with obesity (Chung, 2015).…”
Section: Discussionmentioning
confidence: 99%